The effects of RF coils and SAR supervision strategies for clinically applicable nonselective parallel‐transmit pulses at 7 T. Issue 5 (9th January 2023) - Herrler, Jürgen; Williams, Sydney N.; Liebig, Patrick; Ding, Belinda; McElhinney, Paul; Allwood‐Spiers, Sarah; Meixner, Christian R.; Gunamony, Shajan; Maier, Andreas; Dörfler, Arnd; Gumbrecht, Rene; Porter, David A.; et al.
Abstract : Purpose: To investigate the effects of using different parallel‐transmit (pTx) head coils and specific absorption rate (SAR) supervision strategies on pTx pulse design for ultrahigh‐field MRI using a 3D‐MPRAGE sequence. Methods: The PTx universal pulses (UPs) and fast online‐customized (FOCUS) pulses were designed with pre‐acquired data sets (B0, B1 + maps, specific absorption rate [SAR] supervision data) from two different 8 transmit/32 receive head coils on two 7T whole‐body MR systems. For one coil, the SAR supervision model consisted of per‐channel RF power limits. In the other coil, SAR estimations were done with both per‐channel RF power limits as well as virtual observation points (VOPs) derived from electromagnetic field (EMF) simulations using three virtual human body models at three different positions. All pulses were made for nonselective excitation and inversion and evaluated on 132 B0, B1 +, and SAR supervision datasets obtained with one coil and 12 from the other. At both sites, 3 subjects were examined using MPRAGE sequences that used UP/FOCUS pulses generated for both coils. Results: For some subjects, the UPs underperformed when simulated on a different coil from which they were derived, whereas FOCUS pulses still showed acceptable performance in that case. FOCUS inversion pulses outperformed adiabatic pulses when scaled to the same local SAR level. For the self‐built coil, the use of VOPs showed reliable overestimation compared with the ground‐truth EMF simulations, predicting about 52% lower local SAR for inversion pulses compared with per‐channel power limits. Conclusion: FOCUS inversion pulses offer a low‐SAR alternative to adiabatic pulses and benefit from using EMF‐based VOPs for SAR estimation.